The power of the small: The example of Paracoccidioides brasiliensis conidia (2015)
ABSTRACT: Research on Paracoccidioides brasiliensis has centered in the yeast cell probably because of the lack of distinctive features in the mycelium. In 1942 and for the first time, lateral conidia were noticed in the fungus’ hyphae. Later on, Brazilian, Venezuelan and Argentinean researchers described “aleurias” when the fungus was grown in natural substrates. In 1970 authors became interested in the conidia and were able to obtain them in large numbers and treat them as individual units. Their shape and size were defined and the presence of all the elements of a competent eukaryotic cell were demonstrated. Conidia exhibited thermal dimorphism and, additionally, when given intranasally to BALB/c male mice, they converted into yeasts in the lungs and produce progressive pulmonary lesions with further dissemination to other organs. Studies on the phagocyte-conidia interaction were revealing and showed that these versatile structures allow a better understanding of the host- P. brasiliensis interactions.